Sistem Boarding School dalam Membentuk Kedisiplinan Siswa di SMA Dar El-Iman Islamic Boarding School Kota Padang - Salsabila, Denisa; Rahman, Rini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Education as an effort to form a generation that is intelligent and has good character. One of the good characters that needs to be formed in students is discipline. The education system that can shape student discipline is the Boarding School. Boarding schools are considered to be able to form discipline because students are guided and controlled directly by the dormitory supervisor who lives with the students in the dormitory. This study aims to find out the form of student discipline and the obstacles encountered in forming discipline at SMA Dar El-Iman Islamic Boarding School, Padang City. The method used is a qualitative research method with a type of field research (field research). Sources of data were obtained through in-depth interviews with hostel supervisors and students. To obtain the results of the interviews, the interview guide was used as a research instrument. Data collection techniques used are interviews, observation and documentation. While the data analysis technique is in the form of data reduction, data presentation and drawing conclusions. The findings in this study are; The first form of discipline for Dar El-Iman Islamic Boarding School high school students includes: a) Discipline in worship, students are disciplined in doing the midnight prayer, sunnah fasting, halaqah tahsin tahfidz and muroja`ah Al Qur`an. But lack of discipline in doing congregational prayers. b) Time discipline, some students lack discipline in time. c) Discipline in learning and practice, students are very enthusiastic and disciplined in learning and practicing d) Discipline is clean, tidy, orderly and orderly, overall students are still not clean, neat, orderly and orderly. e) Discipline in guarding the heart, students are disciplined in guarding the heart, that is, it can be seen that students really care about speech, politeness, respect, motivating one another and being honest. Second, the obstacles faced in forming discipline are that students are less consistent in carrying out discipline, adjustments to changes in systems and policies, hard to find examples.